Energy consumption determinants for apparel sewing operations: an approach to environmental sustainability - Islam, Md. Imranul (Kansas State University, 2016)
Fashion is the second most polluting industry and accounts for 10% of global carbon emissions. Consuming fossil fuel based electricity, the primary source of energy in the apparel production process, causes a great deal of greenhouse gas (GHG) emissions. Due to ever-increasing apparel demand and population growth, this industry’s carbon footprint will only grow bigger. As attention on sustainability issues in our world intensifies, research on environmental sustainability in the apparel manufacturing industry is needed. The purpose of this exploratory study was to investigate energy consumption (EC) of the apparel sewing process. The objectives are to (a) identify the most influential EC factors and develop a model to capture EC levels, (b) determine factor interrelationships, (c) identify steps to reduce EC, and (d) explore experts' level of concern regarding EC of the apparel manufacturing and its contribution to greenhouse gas emissions and climate change. A mixed method research study was employed in this study: a qualitative method was utilized to assess expert perceptions and a quantitative method was used to measure EC and build a regression model. This study determined dominant EC and GHG emissions factors from sewing process so that apparel manufacturers can understand which factors need to be controlled to reduce environmental damage. Findings from the study indicated sewing machine motor capacity, sewing speed, and standard allocated minute (SAM) were the most influential EC factors, and shortening the sewing time was found as the best solution to reduce energy consumption in the apparel sewing process. The energy consumption model was found as: Log (EC) = 9.283 + 0.771* log (SAM) + 0.386*knit fabric type + 0.260*sportswear fabric type + 0.080*SPI - 0.008*capacity + 0.004*seam length - 0.001* speed + 0.495 The EC model along with GHG calculator (a tool to convert GHG from EC) will help the industry to determine their EC and GHG emissions level to boost their awareness and to encourage greater impetus for environmental actions. Finally, this study will help designers, retailers, and consumers to pursue environmentally friendly actions in terms of decisions regarding apparel design, sourcing, and purchasing.
Keywords: Energy; Environment; Sustainability; Apparel industry; Sewing